The elderly's perception about the experience violence - Alarcon, Miriam Fernanda Sanches [UNESP]; Damaceno, Daniela Garcia [UNESP]; Cardoso, Bruna Carvalho; Sponchiado, Viviane Boacnin Yoneda; Braccialli, Luzmarina Aparecida Doretto; Sanches Marin, Maria José (Revista Baiana de Enfermagem, 2020)
Objective: To understand the elderly's perception about the experienced violence. Method: Qualitative study, conducted in the Women's Police Station of a city in the countryside of São Paulo. The collection was performed in the period from January to December 2018, with 15 elderly people. The data were analyzed through the thematic analysis technique. Results: Two thematic categories emerged from the reports: the aggression and its impacts and seeking an explanation for the aggressive behavior. Among the perceived aggression, there stood out physical and verbal ones, which turned into negative feelings. However, the elderly still tried to justify the actions of their aggressors. Conclusion: Regarding the violence suffered, the elderly realized that living in a situation of aggression jeopardized their comfort and quality of life.
Keywords: Aged; Aging; Violence